2014
DOI: 10.1890/es13-00270.1
|View full text |Cite
|
Sign up to set email alerts
|

Ground‐dwelling arthropod responses to succession in a pinyon‐juniper woodland

Abstract: Abstract. Stand-replacing wildfire is an infrequent but important disturbance in southwestern pinyonjuniper woodlands. A typical successional cycle in these woodlands is approximately 300 years or more after a stand-replacing fire. Arthropods, especially ground-dwelling taxa, are one of the most abundant and diverse fauna in terrestrial ecosystems and are typically responsive to microhabitat change. Little is known regarding community responses of ground-dwelling arthropods to changes in woodland successional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 50 publications
(57 reference statements)
0
21
3
Order By: Relevance
“…Using the trap design employed by Higgins (2010), pitfall traps were constructed so they could remain in the field for 2 weeks between charging of a trap and collection of specimens. Each pitfall trap consisted of a heavy Pyrex glass ''test tube'' (3.2 cm diameter, 25 cm deep) inserted in a PVC sleeve (3.8 cm in diameter, 28 cm long) buried in the ground.…”
Section: Sampling Protocolmentioning
confidence: 99%
“…Using the trap design employed by Higgins (2010), pitfall traps were constructed so they could remain in the field for 2 weeks between charging of a trap and collection of specimens. Each pitfall trap consisted of a heavy Pyrex glass ''test tube'' (3.2 cm diameter, 25 cm deep) inserted in a PVC sleeve (3.8 cm in diameter, 28 cm long) buried in the ground.…”
Section: Sampling Protocolmentioning
confidence: 99%
“…Finally, in the DM + LC fire group, Solenopsis ants were significantly related to the understory characteristics with an R 2 = 0.93. The relationship of Carabid beetles and two genera of Formicidae to the understory characteristics tested joins a number of reports of the post-fire environmental characteristics affecting these groups [28,56,[80][81][82][83].…”
Section: Resultsmentioning
confidence: 69%
“…Previous work in mixed-conifer forests subjected to prescribe fire [80] and piñon-juniper woodlands affected by wildfire [56] indicates that burning tends to increase the proportion of indicator arthropod taxa. We found similar overall ranges in indicator values as those in these studies, but found a smaller proportion of taxa to be significant indicators following wildfire compared to Higgins et al [56].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations